N.I. VAVILOV’S EXPEDITIONS - N. P. Goncharov (Вавиловский журнал генетики и селекции)
N.I. Vavilov occupies a special position among scientists and most successful «hunters» for cultivated plants and their relatives. He first predicted and then discovered and collected an unexpectedly broad diversity of species, accessions, and varieties. Under his leadership, the most significant bank of plant resources (biodiversity) of crops was established, and later, the collected resources were successfully summoned up for the Soviet economy. The article considers the many-sided Vavilov’s activity to organize and conduct expeditions, in which he took personal part; their goals; efficiency; and basic methods of examination and use of the plants material collected.